TEKANAN INTRA OKULAR POST PERIBULBAR BLOK 5 MENIT DAN 10 MENIT PADA PASIEN VITREKTOMY DI PMN RS MATA CICENDO BANDUNG - Muhammad Firman Saefudin; Roro Lintang Suryani; Murniati Murniati (Viva Medika, 2023)
The peribulbar has a slower anesthetic effect and requires a larger volume than the retrobulbar. Large volumes can increase the pressure on the eye, so that the opening of the vitrectomy operation can cause rapid changes in pressure which can increase the risk of choroidal detachment. The purpose of this study was to determine the description of intra-ocular pressure in vitrectomy patients with peribulbar block at PMN Cicendo Eye Hospital, Bandung. This study used a descriptive research method with a cross sectional approach. The number of samples in the study was 100 respondents, taken by accidental sampling technique. The instrument used was tonopen I Care, then the measurement results were documented and data processing was carried out using the SPSS 26 application. The results obtained showed an increase in IOP in the 5th minute by 18% with a maximum increase of 8 mmHg and a 72% decrease with an average decrease of 3.52 mmHg. Then in the 10th minute, there was a decrease in IOP of 91% with an average decrease of 5.94%, but there was still a maximum IOP increase of 4 mmHg. The decrease in IOP began to occur at 5 minutes and then most of it decreased at 10 minutes even though there was still a 2% increase at 10 minutes this could occur due to other comorbidities of the eye such as glaucoma